Mathematical Applications in Zoology a Concept of Zoo-Mathematics - Gupta, Ashwani Kumar (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
Zoology, often referred to as animal science, involves the study of animals and their life processes. While statistical methods find application in zoological research, the incorporation of mathematics extends beyond statistics. Within various zoological branches such as Ecology, Animal Physiology, Genetics, and Evolution, mathematical formulas play a critical role. While other branches might also leverage mathematics, this paper emphasizes the significance of its application in the aforementioned areas. In Ecology, mathematical formulas underpin investigations into community dynamics, population ecology, ecosystem functioning, and birth and death rates. Animal Physiology delves into chapters on Biochemical Reactions, Diffusion, Osmosis, and Excitability, where mathematical relationships are evident. The paper underscores the profound role of Mathematics and Statistics in elucidating genetics and evolution concepts.